Phosphoinositides: Regulators of Nervous System Function in Health and Disease - Raghu, Padinjat; Joseph, Annu; Krishnan, Harini; Singh, Pramod; Saha, Sankhanil (Frontiers in Molecular Neuroscience, 2019)
Phosphoinositides, the seven phosphorylated derivatives of phosphatidylinositol have emerged as key regulators of multiple sub-cellular processes such as membrane transport, cytoskeletal function and signalling in eukaryotic cells. All of these processes are also present in the cells that constitute the nervous system of animals and in this setting too phosphoinositides are likely to regulate key aspects of cell biology tuned to the unique aspects of cell biology of neurons. Phosphoinositides metabolism and function are mediated by enzymes and proteins that are conserved in evolution and analysis of knockouts of these in animal models implicate this signalling system in neural function. Most recently, with the advent of human genome analysis, mutations that impact components of the phosphoinositide signalling pathway has been implicated in human diseases although the cell biological basis of disease in many cases remains unclear. In this review we evaluate existing evidence for the involvement of phosphoinositide signalling in human nervous system diseases and discuss ways of enhancing our understanding of the role of this pathway in human nervous system function in health and disease.